2021
DOI: 10.1007/s00259-021-05209-2
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FMISO PET/CT imaging of hypoxia as a non-invasive biomarker of disease progression and therapy efficacy in a preclinical model of pulmonary fibrosis: comparison with the [18F]FDG PET/CT approach

Abstract: Purpose Idiopathic pulmonary fibrosis (IPF) is a progressive disease with poor outcome and limited therapeutic options. Imaging of IPF is limited to high-resolution computed tomography (HRCT) which is often not sufficient for a definite diagnosis and has a limited impact on therapeutic decision and patient management. Hypoxia of the lung is a significant feature of IPF but its role on disease progression remains elusive. Thus, the aim of our study was to evaluate hypoxia imaging with [18F]FMISO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…However, the results of this study were disappointingly far from our expectations considering that high levels of hypoxia biomarkers have been found in IPF patients, suggesting a hypoxic microenvironment in the IPF lung [6]. In addition, our group previously suggested that [ 18 F]F-MISO imaging could be a promising tool for early detection and monitoring in a preclinical model of lung fibrosis [7]. Although we are aware that our preclinical results may not be entirely relevant for human IPF, we believe that the study from PORTER et al[1] may suffer from flaws that could explain, at least in part, their underwhelming results.…”
contrasting
confidence: 67%
“…However, the results of this study were disappointingly far from our expectations considering that high levels of hypoxia biomarkers have been found in IPF patients, suggesting a hypoxic microenvironment in the IPF lung [6]. In addition, our group previously suggested that [ 18 F]F-MISO imaging could be a promising tool for early detection and monitoring in a preclinical model of lung fibrosis [7]. Although we are aware that our preclinical results may not be entirely relevant for human IPF, we believe that the study from PORTER et al[1] may suffer from flaws that could explain, at least in part, their underwhelming results.…”
contrasting
confidence: 67%
“…micro-CT and PET/CT) might be helpful within the drug discovery process, in order to increase the reliability of preclinical data and facilitate drug candidates’ translation into the clinic. Even though PET/CT can’t be used for primary screening due to its cost and complexity, this imaging technique could be extremely useful to better profiling the most promising anti-fibrotic drugs before clinical applications, as it enables to investigate the capacity of a drug to modulate the expression of relevant disease biomarkers by using specific probes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated 18 F-FDG uptake could therefore serve as a marker for focal and global inflammatory activation and elevated metabolism in bilateral lungs. In addition, two antifibrotic drugs, namely, nintedanib and pirfenidone, were found to significantly decrease pulmonary FDG uptake in bleomycin-treated mice, indicating the value of PET/CT scans in evaluating the response to antifibrotic medications [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…Compared with conventional HRCT, PET/CT scans seemed to be more intuitive for predicting RP-ILD. In IPF patients, PET/CT scans have been widely studied and found to be valuable for the evaluation of disease activity and therapy efficacy as well as the prediction of disease progression and survival [31,33,34]. In patients with lung cancer, elevated pulmonary FDG uptake is associated with acute exacerbation of ILD after chemotherapy or surgery [35][36][37].…”
Section: Discussionmentioning
confidence: 99%